IMAGING THE AUDIENCE - Lakshmi Srinivas (South Asian Popular Culture Vol. 3, No. 2, October 2005, pp. 101-116, 2005)
Based on participant observation and ethnographic interviews this paper examines the ways in which the popular film business in India anticipates audiences. I explore filmmakers' perceptions of audiences and their attempts to map the audience in the absence of formal market research of the Hollywood variety. Through an identification of conceptualizations and classifications of audiences made by those within the film business, the paper addresses some of the constraints and challenges faced by filmmakers and the related construction of the audience.